2022
DOI: 10.1002/adsc.202101490
|View full text |Cite
|
Sign up to set email alerts
|

“Urea to Urea” Approach: Access to Unsymmetrical Ureas Bearing Pyridyl Substituents

Abstract: A protocol for the synthesis of unsymmetrical ureas substituted by pyridyl/quinolinyl moiety has been developed. This method concluded in metal‐ and base‐free reamination of N,N‐dimethyl‐N‘‐hetaryl ureas with a wide range of aryl and alkyl amines. The isolated yields vary from 40 to 96% depending on the nucleophilicity of the amines. The scope of this method includes more than 50 examples. The reaction is not hindered by either donor or acceptor groups as well as diverse functionalities. The synthesis can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 81 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Note, that 5 in the crystalline state adopts the same curled conformation (see Figure S3 in ESI). Additionally, an intramolecularly bound conformation was previously reported for a related methylsubstituted compound [78] (CCDC code DERXUX). In contrast, the optimized geometry of 4 dg does not contain similar intramolecular hydrogen bonds.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Note, that 5 in the crystalline state adopts the same curled conformation (see Figure S3 in ESI). Additionally, an intramolecularly bound conformation was previously reported for a related methylsubstituted compound [78] (CCDC code DERXUX). In contrast, the optimized geometry of 4 dg does not contain similar intramolecular hydrogen bonds.…”
Section: Resultsmentioning
confidence: 86%
“…Next, we preceded to the functionalization of the synthesized aminocarbonyl derivatives of N ‐oxides. First of all, we checked whether the conditions we proposed earlier [78] for the “urea‐to‐urea” transformation can be used in this case. p ‐Toluidine was taken as a model amine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Boyarskiy et al reported the successful synthesis of 1,2,4-oxadiazoles substituted by pyridine N -oxides [ 115 ], and the N -oxide functionality was compatible with both “ester” and “acid” protocols. Furthermore, these N -oxides were converted into corresponding N -pyridyl ureas [ 115 , 116 ], which are valuable “masked isocyanates” [ 117 , 118 ] and ligands of metal-based anticancer drugs [ 119 , 120 ]. Krasavin et al continued the exploration of 1,2,4-oxadiazole motif for the design of carbonic anhydrase inhibitors [ 14 , 114 ].…”
Section: Base-induced Cyclodehydration Of O -Acyla...mentioning
confidence: 99%